Quantity surveying for Muthalath Al Shuhada School - Mohammad Jehad Qabaha; Adham Raif Bushnaq; Eyad Wael Foqha; Tariq Sharaf Abed (My University, 2020)
The current world has a huge movement of large scale projects, making the need of analyzing systems and approaches more necessary. In Palestine, as in other countries, the construction sector is very important element for the economic growth as it develops social and cultural sector and creates more job opportunities in the society. One of the important aspects in the construction sector is the quantity surveying for project in a detailed and approximate as well as the division of construction work into several activities that can be better controlled and easier to achieve. In this project we will make a quantity surveying in detailed for a new building of MOTHALATH ALSHOHAD’ school in Jenin Governorate. Many software will be used in this project, mainly Revit software to calculate quantities, estimate cost and drawing 3D building, primavera p6 will be used for scheduling project time and Naviswork. The main objectives of this project are: 1.Reviewing the main construction design plans and diagrams. 2.Calculating quantities, detailed costs and scheduling project time in order to minimize cost and time to the lower limit. 3.Finally comparing the calculated time and cost with the actual ones from the contractor of the project.